KONSTRUKSI TINDAK PIDANA BERITA BOHONG (HOAX) DALAM UNDANG-UNDANG ITE - Syaidah Novia Sari (Program Magister Hukum Universitas Lambung Mangkurat, 2021)
The research aims: 1) To know the construction of hoax criminal acts referred to in the ITE Law. 2) To find out the formulation policy for the future (ius constituentum) in hoax crime. This research is normative legal research. While the type of research is research with emphasis on problems that often arise related to the principle of law with regard to the meaning and scope of criminal acts of hoax in the ITE Law.The results of the study concluded: first, Article 28 paragraph (1) of Law Number 11 of 2008 concerning Information and Electronic Transactions (